New properties of the switching points for the generalized Hukuhara differentiability and some results on calculus ? - Chalco-Cano, Y.; Costa, T. M. [UNESP]; Roman-Flores, H.; Rufian-Lizana, A. (Elsevier B.V., 2021)
This article provides a new characterization of the switching points for generalized Hukuhara differentiability and shows that the set of all switching points is at most countable. Using these results, new properties in differential calculus, which generalize previous results, are presented. Then, generalizations of Ostrowski type inequalities for interval-valued functions using weaker assumption than previous results are obtained, and new numerical integration methods for interval-valued functions are established. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Generalized Hukuhara differentiability; Fuzzy numbers-valued functions; Switching points for generalized Hukuhara differentiability